2013
DOI: 10.1007/s11916-013-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Make Migraines Worse and Tension Type Headaches Better?

Abstract: Many non-pharmacological treatments have been implicated in the treatment of primary headache, with exercise being a common recommendation. In this review we first provide an overview of the relationship between exercise and primary headaches. We then review the physiology of pain modulation, with focus on the endogenous opioids, endocannabinoids, and neuropeptides calcitonin gene-related peptide (CGRP) and brain-derived neurotrophic factor (BDNF), and their associations with primary headache and exercise. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…The program in total should remain in a tolerable level preventing exercise-related pain and disability, with a suggested frequency of two to three times per week. Patients must continue with this despite initial lack of improvement because it is found that people with migraine can develop a “tolerance” to the pain-inducing effects of moderate exercise [ 109 ].…”
Section: Methodsmentioning
confidence: 99%
“…The program in total should remain in a tolerable level preventing exercise-related pain and disability, with a suggested frequency of two to three times per week. Patients must continue with this despite initial lack of improvement because it is found that people with migraine can develop a “tolerance” to the pain-inducing effects of moderate exercise [ 109 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is important to consider that there are two different exercise strategies; (1), aerobic exercises; and (2), local exercises targeting specific musculoskeletal disorders of the cervical spine. This differentiation is clinically relevant since aerobic exercises could be the best option in migraine prophylaxis, whereas specific neck/shoulder strengthening exercises may be a potential better choice for TTH [61]. This assumption is based on the presence of motor output changes of the cervical musculature, e.g., reduced neck muscle strength [62], an increased co-activation of the superficial cervical muscles [63], in patients with TTH.…”
Section: Scientific Evidence Of Exercise Interventions For Headachesmentioning
confidence: 99%
“…Our review of the medical literature did not identify studies investigating the combined effects of these three domains of RLB. Previous studies have investigated one domain alone, i.e., either sleep [5,18], exercise [6,11], or mealtime [15]. The purpose of the present study is to address this by investigating the connection between the RLB triumvirate and migraine.…”
Section: Introductionmentioning
confidence: 98%
“…Maintenance of biological rhythms is important in maintaining health, i.e., ultradian (e.g., feeding cycles) [2], circadian (e.g., cycles of sleep, digestive secretions, bowel movements) [3], infradian (e.g., menstrual cycles) [3], and diurnal rhythms (circadian rhythms synchronized with day-night cycle) [4]. Lifestyle behaviors of sleep [5], exercise [6][7][8], mealtime pattern [9] and hydration status [10] are known to independently affect migraine occurrence. Individual-customized daily aerobic exercise, daily scheduled stress management and relaxation techniques, and mindfulnessbased stress reduction prevent migraine [5], while inadequate sleep hygiene, non-restorative sleep, skipping meals, and dehydration can trigger migraine [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%